Race and ethnicity in the United States - Luhman, Reid (Harcourt College Publishers, 2002)
This unique text highlights ethnic group interactions and approaches contemporary issues from an institutional perspective. Combining historical, theoretical and comparative approaches to the study of race and ethnicity, this book will help students understand the origin of contemporary racial and ethnic groups and the importance of the past for understanding all groups